Classic and modern fabrics : the complete illustrated sourcebook - Wilson, Janet (New York : Thames & Hudson, 2010)
A guide to different types of fabric in circulation. It describes over 600 examples, from classic tweeds to nano fabrics. It is suitable for design students, teachers, designers, historians, manufacturers, buyers and merchandisers worldwide.
Includes bibliographical references.
boek